Bioavailability of Selenocystine Complex in Ten Healthy Volunteers Using Flameless Atomic Absorption Spectrophotometer - Ali Mahmoud, Waleed (Asian Journal of Chemistry, 2012)
The synthesis of selenocystine complex was formulated as 200 mcg tablet, to study the bioavailability of selenocystine complex in human sera of ten healthy volunteers investigated using flameless atomic absorption spectrophotometer. The selenocystine concentrations were measured at different intervals times from 0, 1, 1.5, 2, 2.5, 3, 3.5, 4 h. The concentrations time curve was constricted. The result observed that the maximum concentration was 135.3 ng/mL reached after 1.5 h of ingested tablet. The selenocystine complex was excreted through 4 h.